Revealing How Indonesia’s Subnational Governments Spend Their Money on Education : Indonesia Subnational Education Public Expenditure Review 2020 - Afkar, Rythia (World Bank, Washington, DC, 2020)
Indonesia’s most recent amendment to its decentralization legislation transferred a far greater role in education management and service delivery to subnational governments. However, little information has been made available on how subnational governments conduct the planning, allocation, and execution of their education budgets—a key driver of increased human capital development. This study aims to fill this essential information gap by assessing the activities implemented by subnational governments as they fulfill their mandate in the education sector. Data collected from January to June 2019 in a survey of 27 districts and cities spread over eight provinces, as well as an analysis of national spending data.